2012
DOI: 10.1155/2012/381974
|View full text |Cite
|
Sign up to set email alerts
|

Centella asiaticaExtract Improves Behavioral Deficits in a Mouse Model of Alzheimer's Disease: Investigation of a Possible Mechanism of Action

Abstract: Centella asiatica (CA), commonly named gotu kola, is an Ayurvedic herb used to enhance memory and nerve function. To investigate the potential use of CA in Alzheimer's disease (AD), we examined the effects of a water extract of CA (GKW) in the Tg2576 mouse, a murine model of AD with high β-amyloid burden. Orally administered GKW attenuated β-amyloid-associated behavioral abnormalities in these mice. In vitro, GKW protected SH-SY5Y cells and MC65 human neuroblastoma cells from toxicity induced by exogenously ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
114
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 32 publications
9
114
0
Order By: Relevance
“…In various studies testing cognitive improvements of rats and standard shuttle box, step-through paradigm, elevated plus maze and passive avoidance tests, C. asiatica improved learning and memory [10]. When aqueous extracts of C. asiatica at doses of 100-300 mg/kg per day were distributed to newborn mice from 15 days old to 30 days old, learning and spatial memory were improved without influencing motor functioning skills [10].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…In various studies testing cognitive improvements of rats and standard shuttle box, step-through paradigm, elevated plus maze and passive avoidance tests, C. asiatica improved learning and memory [10]. When aqueous extracts of C. asiatica at doses of 100-300 mg/kg per day were distributed to newborn mice from 15 days old to 30 days old, learning and spatial memory were improved without influencing motor functioning skills [10].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…When aqueous extracts of C. asiatica at doses of 100-300 mg/kg per day were distributed to newborn mice from 15 days old to 30 days old, learning and spatial memory were improved without influencing motor functioning skills [10]. Soumyanath et al reported that doses of C. asiatica influenced the cell nerves of the pyramidal cells in the prefrontal cortex, the hippocampus, and other areas, in newborn and adult mice and rats [10]. Soumyanath et al suggest that results from these studies presents aqueous extract of C. asiatica as lowering the degenerative impairments of memory, learning and aging in relation to Alzheimer's disease [10].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 3 more Smart Citations